Analysis of High School Students’ Learning Styles in Biology Material - Indriani, Bella Cindy; Agustini, Mira Mariana (Jurnal Report of Biological Education, 2024)
Background: The background of this research there has been no mapping of students’ learning styles, so that the implementation of differentiated learning has not been optimal. Method: This study uses a quantitative descriptive approach with 25 students in grades X, XI, and XII of SMA Muhammadiyah Kota Sukabumi as research subjects. This instruments used in this study include a learning style questionnaire and teacher interview guidelines. Result: The result of the analysis of the analysis of the learning styles of all students of SMA Muhammadiyah Sukabumi in the 2023/2024 academic year are visual 64,37%, auditory 28,37%, kinesthetic 5,29%, a combination of visual and auditory 1,96%. Conclusion: This study shows that the learning syles of students at SMA Muhammadiyah Sukabumi are diverse, with a dominancw of visual learning styles, followed by auditory and kinesthetic. This finding emphasizes the importance of implementing differentiated learning to meet the individual needs of students. In the context of the independent curriculum, learning strategies that consider learning styles can improve student motivation and learning outcomes, especially in Biology subjects. Keywords : Learning style, visual, auditory, kinesthetic